Designing for Durable Learning in Blended Education: An Evidence-Informed Framework Integrating Retrieval Practice, Feedback, and Cognitive Load - Gizem Arslan Gizem Arslan (Kalam Practica Media, 2025)
Blended and online learning environments have expanded rapidly across higher education and professional training contexts worldwide, yet a substantial proportion of their instructional designs continue to prioritize content delivery over the conditions that produce durable, transferable learning. Evidence accumulated across decades of learning sciences research consistently demonstrates that long-term retention and meaningful transfer depend not on the volume of information to which learners are exposed but on how they practice retrieving that information, how they receive and act on actionable feedback, and how cognitive demands are managed during learning activities to ensure that available mental resources are directed toward deep rather than superficial processing. This evidence-informed conceptual paper synthesizes three complementary bodies of empirical scholarship, the testing effect and retrieval practice literature pioneered by Roediger and Karpicke, the formative assessment and feedback research synthesized by Black and Wiliam and elaborated by Hattie and Timperley, and cognitive load theory as developed by Sweller and extended to multimedia learning contexts, to propose a practical design framework for durable blended learning. The framework articulates four interdependent domains: (a) retrieval-rich task sequences that embed spaced, interleaved, and low-stakes retrieval as the default learning activity rather than as an occasional supplementary check; (b) feedback loops structured to support revision and self-regulation rather than merely to evaluate performance; (c) cognitive load-sensitive multimedia and pacing decisions that reduce extraneous processing demands while preserving the generative challenge that deep learning requires; and (d) equity-by-design supports that ensure retrieval and feedback mechanisms are accessible and inclusive across the full diversity of learner characteristics and circumstances. Three tables present empirical data on retrieval practice effect sizes across design conditions, feedback type effectiveness across common learning bottlenecks, and implementation quality indicators with measured outcomes from blended learning research. The paper concludes with recommendations for instructional designers, teachers, and program leaders seeking to improve learning outcomes without relying on simplistic engagement proxies.